LP-HT anatectic processes and lithological heterogeneity in the Mindelo Migmatite Complex (NW Portugal) - Areias, M. (2014)
The Mindelo Migmatitic Complex crops out in the coastal zone north of Porto (Portugal) and consists of a set of migmatitic and granitic lithologies. Field relationships, petrography, geochemistry and isotopic signature of the various lithologies allow inferring the sequence of anatectic processes that resulted in their characteristic lithological heterogeneity. The metasedimentary sequences (Schist-Greywacke Complex) show chemical composition and isotopic signature identical to the metatexites. Therefore, it is suggested to be the protolith of Mindelo Migmatite Complex lithologies. The melting has occurred in several structural levels and thus at different pressure and temperature conditions, resulting in rocks with specific characteristics. In shallow levels (<3.5 kbar) metatexites are formed essentially by fluid-present partial melting followed by fluid-absent incongruent biotite melting producing peritectic cordierite, quartz, plagioclase and minor amounts of K-feldspar. The melt segregation led to its crystallization in dilatant sites forming masses and veins of leucogranite. In slightly deeper levels the melting rate is higher which leads to the formation of diatexites and two mica granites that intruded metatexites. This material rises in the crust and incorporates abundant xenoliths forming a very heterogeneous granitic body. Tourmalinization of granitoids, migmatite and metasediments occurred at subsolidus conditions associated with aplite-pegmatites that cut all the other lithologies. A last aqueous fluid influx led to muscovitization of metatexites,granitoids and metasediments. The migmatization started after the first ductile deformation phase of Variscan Orogeny (D1) and was continuously active during the following stage of deformation and shear (D3). The several pulses of different fluids that affected the Mindelo Migmatitic Complex probably are related to the emplacement of the syn and late- D3 variscan granites. The Mindelo Migmatite Complex represents an example of migmatites formed in low pressure conditions and illustrates some of the reactions involving melting in high grade pelitic rocks and subsequent mineral alterations due to infiltration of late different fluids.